2010
DOI: 10.1002/cyto.b.20543
|View full text |Cite
|
Sign up to set email alerts
|

Non‐CLL‐like monoclonal B‐cell lymphocytosis in the general population: Prevalence and phenotypic/genetic characteristics

Abstract: Background: Monoclonal B-cell lymphocytosis (MBL) indicatesMethods: PB samples from 639 healthy individuals (46% men/54% women) >40 years old (62 6 13years) with normal lymphocyte counts (2.1 6 0.7 3 10 9 /L) were immunophenotyped using high-sensitive flow cytometry, based on 8-color stainings and the screening for >5 3 10 6 total PB leukocytes.Results: Thirteen subjects (2.0%; 9 males/4 females, aged 73 6 10 years; absolute lymphocyte count: 2.4 6 0.8 3 10 9 /L) showed a non-CLL-like clonal B-cell population,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 29 publications
3
30
4
3
Order By: Relevance
“…In contrast, about 50% of the individuals harboring atypical CLL MBL and MBL CD5 (À) at the time of diagnosis lost this condition within 3 years, indicating that the presence of these cells is transient in nature. These results differed from a previous study (7) in which 12 atypical CLL MBL and MBL CD5 (À) cases were shown to persist 1 year after the initial diagnosis. According to our model, these seemingly different findings are not contradictory.…”
Section: Interpreting Data That Document the Presence Of Cancerassocicontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast, about 50% of the individuals harboring atypical CLL MBL and MBL CD5 (À) at the time of diagnosis lost this condition within 3 years, indicating that the presence of these cells is transient in nature. These results differed from a previous study (7) in which 12 atypical CLL MBL and MBL CD5 (À) cases were shown to persist 1 year after the initial diagnosis. According to our model, these seemingly different findings are not contradictory.…”
Section: Interpreting Data That Document the Presence Of Cancerassocicontrasting
confidence: 99%
“…To test this notion, cohorts of healthy people that harbor aberrant cells should be followed longitudinally to determine the fate of these cells, i.e., whether their presence is transient or not. This analysis can be performed using the same experimental techniques described in the studies discussed above (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). When testing for the presence of aberrant cells in the blood, the average telomere length should be determined both in the aberrant cells and in the normal cells of these individuals (in blood average, telomere length can be efficiently measured using flow FISH cytometry; ref.…”
Section: Translatable and Testable Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results differ from those recently published in a series of 12 atypical-CLL and CD5 Ϫ MBL reevaluated 12 months after the first immunophenotypic analysis. 24 All clones were confirmed and even showed a significant increase in the median concentration of clonal B cells. Although this discrepancy may be accounted for both by the original higher median value of the clonal populations and especially by the different length of the follow-up, further studies with larger cohorts are needed to settle the issue.…”
Section: Discussionmentioning
confidence: 89%
“…Instrument setup, calibration, and daily monitoring were performed according to well-established protocols [23]. MBL classification into CLL-like and non-CLL-like MBL categories were based on consensus criteria [4,24,25]. The following B-cell populations were identified [15,16]: immature B-cells: CD10 1 CD19 1 CD20 1 CD27 -CD38 1 ; naive B-lymphocytes: CD10 -CD19 1 CD20 1 CD27 -CD38 -IgM 1 ; memory B-lymphocytes: CD10 -CD19 1 CD20 1 CD27 1 CD38 -; and plasmablasts: CD10 -CD19 1 CD20 -/ 1d CD27 hi CD38 hi ).…”
Section: Methodsmentioning
confidence: 99%